2017
DOI: 10.1084/jem.20170438
|View full text |Cite
|
Sign up to set email alerts
|

CD55 regulates self-renewal and cisplatin resistance in endometrioid tumors

Abstract: CD55 is a membrane complement regulatory protein that attenuates complement-mediated cytotoxicity. Saygin et al. elucidate a new role for CD55 as a signaling hub for cancer stem cell self-renewal and cisplatin resistance pathways in endometrioid tumors and open a new line of research into chemotherapeutic-refractory cancers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 34 publications
9
103
0
6
Order By: Relevance
“…Such modulatory effects of JNK on responses to chemotherapies and targeted therapies were also observed in gastric cancer [86], hepatocellular carcinoma [87], head and neck cancer [88], endometrial cancer [89], and ovarian cancer [90]. An interesting finding in this context is that JNK signaling seems specifically important for the maintenance of cancer stem cells in different cancer types including pancreatic [91], endometrial [92], and ovarian cancer [93]. In ovarian cancer, the mechanism involves upregulation of survivin, an antiapoptotic protein that protects stem cell viability [94].…”
Section: Jnk Enhancing Resistance To Erk Pathway Inhibitors and Chemomentioning
confidence: 83%
“…Such modulatory effects of JNK on responses to chemotherapies and targeted therapies were also observed in gastric cancer [86], hepatocellular carcinoma [87], head and neck cancer [88], endometrial cancer [89], and ovarian cancer [90]. An interesting finding in this context is that JNK signaling seems specifically important for the maintenance of cancer stem cells in different cancer types including pancreatic [91], endometrial [92], and ovarian cancer [93]. In ovarian cancer, the mechanism involves upregulation of survivin, an antiapoptotic protein that protects stem cell viability [94].…”
Section: Jnk Enhancing Resistance To Erk Pathway Inhibitors and Chemomentioning
confidence: 83%
“…The clinical outcome of dystrophic scoliosis patients treated with posterior-only fusion by using hooks and rods demonstrated that the pseudarthrosis rate was high and curve progression was common [17]. Recently, some good results of posterior only fusion surgeries in NF-1 patients with dystrophic scoliosis have been reported [9,10,19]. In this study, we reported our results about the posterior only fusion procedure in NF-1 patients with EOS.…”
Section: Discussionmentioning
confidence: 88%
“…There was no neurological complication (transient or permanent neurological deficiency) observed. Given the facts that the complication rate of anterior-posterior approach is as high as 64%, the probability of perioperative pulmonary dysplasia is as high as 45%, and the fact that lung injury and dural tear are also seen during the precedure [19,20], we suggest that posterior fusion surgery be a good alternative way to get a better postoperative outcome and reduce the postoperative complications.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the most recent, a study pointed that cancer stem cells are responsible for cancer proliferation and chemoresistance [20], it was found that SPARC-related modular calcium binding 2 (SMOC-2) drive the endometrial cancer chemoresistance functional as a endometrial cancer stem cell molecule. Similarly, Caner Saygin et.al reported that CD55, as unique signaling node, drives self-renewal and chemoresistance in endometrioid cancers [29]. Other study found that autophagy also involves in chemoresistance [30].…”
Section: Discussionmentioning
confidence: 91%